2012
DOI: 10.1116/1.4764110
|View full text |Cite
|
Sign up to set email alerts
|

Active layer thickness effects on the structural and electrical properties of p-type Cu2O thin-film transistors

Abstract: The authors investigated the effects of active layer thickness on the structual, optical, and electrical characteristics of p-type Cu2O thin-film transistors (TFTs). It was observed that as the channel thickness increases, the average grain size and root mean square roughness of the Cu2O thin films increase, but the optical transmittance notably decreases, especially in the short wavelength range below 500 nm. The p-type Cu2O TFT device exhibits the cleanest transfer function with only a small subthreshold slo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 23 publications
1
28
0
Order By: Relevance
“…Research on Cu 2 O has a long history, and the fabrication of Cu 2 O thin films or nanostructures has been widely reported by various techniques, such as PLD, magnetron sputtering, and thermal oxidation; and chemical routes, such as electrodeposition, spin coating, atomic‐layer deposition, spray coating, molecular‐beam epitaxy, microwave irradiation from a Cu precursor, chemical vapor deposition, and ink printing . A summary of the most promising studies on binary copper oxide thin films is shown in Table 2 .…”
Section: Discovery and Synthesis Of Hole‐transporting (P‐type) Oxidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on Cu 2 O has a long history, and the fabrication of Cu 2 O thin films or nanostructures has been widely reported by various techniques, such as PLD, magnetron sputtering, and thermal oxidation; and chemical routes, such as electrodeposition, spin coating, atomic‐layer deposition, spray coating, molecular‐beam epitaxy, microwave irradiation from a Cu precursor, chemical vapor deposition, and ink printing . A summary of the most promising studies on binary copper oxide thin films is shown in Table 2 .…”
Section: Discovery and Synthesis Of Hole‐transporting (P‐type) Oxidesmentioning
confidence: 99%
“…Nam et al studied the effect of active‐layer thickness on p‐type Cu 2 O TFTs . Staggered bottom‐gate TFTs were built on a Si substrate with 100 nm of thermally grown SiO 2 as the dielectric layer, while Ni was evaporated as the top contact.…”
Section: Performance Of P‐type Oxide Thin‐film Transistorsmentioning
confidence: 99%
“…75,298,299 Moreover, doping of n-type metal oxide semiconductors has enabled the demonstration of p-type TFTs based on P-and N-doped ZnO NW, 259,300 as well Ga 2 O 3 :Zn. 70 Among all the reported p-type metal oxide semiconductor TFTs, [70][71][72][73][74][75]79,[280][281][282][283][284][285][286][287][288][289][290][291][292][293][294]300 only few devices have been fabricated on flexible substrates. 36,79,257,267,272,273,285,289 This is mainly due to the high deposition and annealing temperatures (typically !200 C) that are required, which are incompatible with flexible temperature-sensitive substrates.…”
Section: A P-type Metal Oxide Semiconductorsmentioning
confidence: 99%
“…In this case, the driving force for the nucleation growth was increased at a given annealing temperature. For the polycrystalline MOS films, the enhanced crystallinity would certainly decrease the number of trapping centers and carrier scattering events, which is beneficial to the carrier transport along the conducting channel inside the films …”
Section: Key Parameters Of Cu:nio Tfts Fabricated Under Various Condimentioning
confidence: 99%
“…The representative transfer characteristics of Cu:NiO TFTs as a function of the Cu ratio are shown in Figure a. The small counterclockwise hysteresis (<0.1 V) indicates that there are small amounts of traps within the Cu:NiO channel layers and at the interface of Cu:NiO/ZrO 2 . The extracted device parameters, i.e., hole mobility (μ h , FE ), on–off current ratio ( I on / I off ), threshold voltage ( V TH ), and subthreshold swing (SS), are summarized in Table 1 .…”
Section: Key Parameters Of Cu:nio Tfts Fabricated Under Various Condimentioning
confidence: 99%